Network pharmacology, molecular docking, and experimental validation to explore the potential mechanism of Long Mu Qing Xin mixture for the treatment of attention deficit hyperactivity disorder - Li, Xuejun; Xiao, Zhen; Pu, Wenyan; Jiang, Zhiyan; Wang, Shumin; Zhang, Yixing (Frontiers in Pharmacology, 2023)
The clinical efficacy of Long Mu Qing Xin Mixture (LMQXM) has been established in the treatment of attention deficit hyperactivity disorder (ADHD); however, the mechanism of action is still not fully understood. This study aimed to predict the mechanism of LMQXM for ADHD using network pharmacology and molecular docking, which were then validated using animal experiments. This study showed that beta-sitosterol, stigmasterol, rhynchophylline, baicalein, and formononetin might be key components of LMQXM for ADHD, and that these components bind well to the core targets dopamine (DA) receptors (DRD1 and DRD2). Furthermore, LMQXM might act through the DA and cAMP signaling pathways. To verify the above mechanistic hypothesis, the spontaneously hypertensive rats (SHRs), were randomly divided into 5 groups: model group (SHR), methylphenidate hydrochloride group (MPH, 4.22 mg/kg), and 3 LMQXM groups (low-dose (LD) group, 5.28 ml/kg; medium-dose (MD) group, 10.56 ml/kg; high-dose (HD) group, 21.12 ml/kg), and administered by gavage for 4 weeks; the WKY rats were set as the control group. The open field test (OFT) suggested that LMQXM-MD and LMQXM-HD control the hyperactivity and impulsivity; learning memory was significantly improved in LMQXM-MD group vs. SHR based on the Morris water maze (MWM) test. We found that LMQXM-MD upregulated DA levels, mean optical density (MOD) and mRNA expression of DRD1, cAMP and PKA in the prefrontal cortex (PFC) and striatum, while LMQXM-LD and LMQXM-HD upregulated DA levels in the striatum and MOD of cAMP and PKA mRNA expression in the PFC. However, we did not find a significant regulatory effect of LMQXM on DRD2. To sum up, this study demonstrated that LMQXM increases DA levels mainly by activating the cAMP/PKA signaling pathway through DRD1, thereby controlling the core symptoms of ADHD, and was most effective at moderate doses, while higher doses did not enhance its therapeutic effect.